Do tablets cure the pedagogy headache? - Paul Hopkins (Educational Futures)
Tablet devices have made a huge impact in schools and in 2015 they were predicted to outsell personal computers (Gartner, 2014). 70 per cent of UK schools are estimated to be using tablets (BBC, online) and across Europe, “laptops, tablets and net-books are becoming pervasive” (EU schoolnet, 2014). As these devices become established in schools they both support and develop existing practice (Burden, Hopkins, Male, Martin and Trala, 2012; Baran, 2014), but are also starting to challenge some existing models of thinking and pedagogy (Fullan and Langworth, 2014; Kearney, Schuck, Burden and Aubusson, 2012) and also teachers’ attitudes towards learning and teaching (Ertmer, 1999; Burden and Hopkins, 2015). In offering opportunities for learning to become more authentic, personal and collaborative (Kearney et al., 2012) there are opportunities for teachers to start to redesign the ways in which learning is taking place (Puentedura, 2010; McCormick and Scrimshaw, 2001). Traxler defines mobile learning as “an educational process, in which handheld devices or palmtops are the only or dominant used technology tools” (2007: 2) and Kearney et al. (2012) argue that it has the potential to revolutionise the learning process in allowing individuals to determine their own independent paradigms and frameworks of learning. These devices are also sophisticated producers of digital artefacts and children and teachers are capable of being co-producers of learning materials.